Feedback suppression in reliable multicast protocol - Cheng, Liang. (2008)
In this thesis we present an effective end-to-end NACK suppression algorithm that could solve the problem caused by correlated packet loss and independent packet loss among receivers. It combines representatives with timers to suppress NACKs. Representatives are a small set of group members providing fast feedback to the source and help suppress feedback from other members. Timers are periods set at receivers which experience packet loss to slot feedback in different time. NACKs from representatives would be expected to suppress NACKs caused by the correlated packet loss in a small number of particularly lossy links. And timer settings are likely to limit NACKs from a large number of slightly lossy links. Exponentially distributed timer is selected as the choice of timer settings because analysis and simulation results show that exponentially distributed timer choice outperforms uniformly distributed timer choice in NACK suppression. Simulation results show that our algorithm could effectively reduce the number of NACKs at the sender, thus solving the NACK implosion problem.